PRIMA-1 targets the vulnerability of multiple myeloma of deregulated protein homeostasis through the perturbation of ER stress via p73 demethylation - Teoh, Phaik Ju (Oncotarget, 2016)
Despite therapeutic advancement, multiple myeloma (MM) remains incurable with drug resistance being one of the main challenges in the clinic. Myeloma cells possess high protein secretory load, leading to increased intracellular endoplasmic reticulum (ER) stress. Hence, they are vulnerable to further perturbation to its protein homeostasis. In studying the therapeutic mechanism of PRIMA-1 (mutant-p53-reactivating-agent), we uncovered its novel p53-independent-mechanism that can be exploited for myeloma. Despite its inability in restoring the wild type-p53 protein conformation and transcriptional function in the mutant-p53-human-myeloma-cells, PRIMA-1 was efficacious against myeloma cells with differential p53 genotypes. Strikingly, cells without p53 expression demonstrated highest drug sensitivity. Genome-wide gene-expression analysis revealed the involvement of ER stress/UPR-pathway in inducing PRIMA-1-toxicity. UPR markers, HSP70, CHOP and GADD34, were significantly up-regulated, concomitantly with the induction of apoptosis. Furthermore, there was a global attenuation of protein synthesis, correlated with phospho-eIF2a up-regulation. Mechanistically, we identified that PRIMA-1 could cause the demethylation of TP73, through DNMT1 depletion, to subsequently enhance UPR. Of clinical significance, we observed that PRIMA-1 had additive therapeutic effects with another UPR-inducing-agent, bortezomib. Importantly, it can partially re-sensitize bortezomib-resistant cells to bortezomib. Given that MM is already stressed at the baseline in the ER, our results implicated that PRIMA-1 is a potential therapeutic option in MM by targeting its Achilles heel.